Experiences and pedagogy: a qualitative case study that examines teaching experiences, philosophies, and best practices of University Distinguished Teaching Scholars at Kansas State University - Vaca-Cárdenas, Mónica Elva (Kansas State University, 2017)
This qualitative case study examined how successful professors who were awarded the Coffman Chair for University Distinguished Teaching Scholars at Kansas State University describe their teaching experiences, philosophies, and best practices in undergraduate teaching and learning. Educators today are concerned about what are the best practices to educate new generation students to survive in a rapidly changing world. Additionally, because most research focus on best practices on the implementation or evaluation of a specific methodology, method, or strategy in one particular course or program, this research addressed the need to investigate the teaching experiences, philosophies, and best practices of outstanding award winner professors in different areas; to understand the challenges they face and the ways they handle undergraduate teaching and learning. This qualitative case study was informed by Critical Theory as the theoretical framework, grounded in Constructivism, because critical theory cares about social justice while abandoning obsolete, elitist and antidemocratic features of traditional concepts of education. Seven distinguished teaching scholars, who belong to Psychological Sciences, School of Integrated Studies, Political Sciences, Horticulture and Natural Resources, Modern Languages, English, and Physics departments, voluntarily participated in this study. Multiple methods were used to collect data including demographic questionnaires, semi-structured interviews (time line elicitation interviews, formal interviews, and photo elicitation interview), analysis of documents, and journaling. Seven themes emerged from my findings. The first theme identified the influential people and struggles encountered by professors when they were students. The second identified events that led professors in choosing their major, why they became teachers, and their teaching strengths and passions. The third identified the challenges they face when teaching undergraduate students and mentoring support received as professors. The fourth identified how participants described themselves as successful professors and the way they organize and balance their academic and personal life. The fifth identified specific educational theories the professors apply in their teaching, the insights of their teaching philosophies, and their thoughts about the importance of education. The sixth identified the way professors decide the curriculum to teach and the way they evaluate their students. Finally, the seventh theme identified the significant work they did as recipients of the Coffman Chair for University Distinguished Teaching Scholar, and their teaching best practices. Recommendations for practice and future research were also addressed. Thus, this study contributes to the understanding of teaching experiences, philosophies, and best practices of successful professors in undergraduate teaching and learning, based on evidence which is the personal experiences of the participants for the benefit of every person involved in education.
Keywords: Teaching and learning; Teaching experiences; Teaching philosophies; Teaching best practices; Pedagogy; Undergraduate